2009
DOI: 10.3238/arztebl.2009.0641
|View full text |Cite
|
Sign up to set email alerts
|

The Morbidity and Mortality Associated With Overweight and Obesity in Adulthood

Abstract: The prevailing notion that overweight increases morbidity and mortality, as compared to so-called normal weight, is in need of further specification. Obesity, however, is indeed associated with an elevated risk for most of the diseases studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
0
28

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(137 citation statements)
references
References 74 publications
2
107
0
28
Order By: Relevance
“…Recently, the World Health Organization definition for overweight has been questioned by several studies which showed that overweight (BMI between 25.0 and 30 kg/m 2 ) was not associated with increased risk of death (Flegal et al, 2005;McGee and Diverse Populations Collaboration, 2005;Lenz et al, 2009). The controversy between previous studies may be because of the differences in study design and study populations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the World Health Organization definition for overweight has been questioned by several studies which showed that overweight (BMI between 25.0 and 30 kg/m 2 ) was not associated with increased risk of death (Flegal et al, 2005;McGee and Diverse Populations Collaboration, 2005;Lenz et al, 2009). The controversy between previous studies may be because of the differences in study design and study populations.…”
Section: Introductionmentioning
confidence: 99%
“…Basic model included the SF-12 summary score at all time points as the dependent variable and baseline BMI, change in BMI from baseline to all follow-up points, age, sex, study arm, interaction term time 6 study arm, and time-dependent smoking status as independent variables, n = 6726. 4 Further adjusted model consisting of the basic model additionally adjusted for education level, employment status, living situation, diagnosis of diabetes and hypertension, and history and time-dependent cumulative incidence of myocardial infarction/stroke and coronary artery bypass grafting/percutaneous coronary intervention within the previous 6 months, n = 6682. individuals with a high risk for cardiovascular diseases. In the cross-sectional analyses, BMI was inversely associated with physical and mental HRQoL, measured by the SF-12 health status instrument.…”
Section: Discussionmentioning
confidence: 99%
“…In Table 1, the baseline characteristics including the Basic model included the SF-12 summary score at baseline as the dependent variable and baseline BMI, age, sex, and smoking status at baseline as independent variables, n = 6726. 4 Further adjusted model consisting of the basic model additionally adjusted for education level, employment status, living situation, diagnosis of diabetes and hypertension, and history of myocardial infarction, stroke, coronary artery bypass grafting, and percutaneous coronary intervention at baseline, n = 6682. …”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…As an option for treatment of obesity, it makes possible an improvement in quality of life, and a reduction in the worldwide death in this population which may be more than 200% when compared with eutrophic individuals (6) .…”
Section: Introductionmentioning
confidence: 99%